Rancang Bangun dan Analisis Jig Welding Pengelasan Siku Sebagai Alat Bantu Praktikum Produksi Jig & Fixture di Politeknik STMI Jakarta - Nurhadi, Fadhil Fadhlurrohman; Purbaningrum, Sanurya Putri; Solih, Edwin Sahrial; Rifai, Ahmad; Al Fatir, Aditya; Yudhistira, Hilmi; Satriatama, Adrian (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Angular welding is a commonly utilized technique in the manufacturing industry, particularly in the construction of frame structures. The primary challenge in angular welding is ensuring the accuracy of the angles and the strength of the joints. At Polytechnic STMI Jakarta, the Jig & Fixture Production course aims to train students in using appropriate manufacturing techniques and tools, including welding jigs. The use of welding jigs can improve the precision, efficiency, and consistency of welding results, while also reducing the risk of human error. This study aims to design and analyze a welding jig for angular welding in the context of practical coursework at STMI Jakarta Polytechnic. The research methodology includes a literature review, jig design using CAD software, prototype development, and performance testing and analysis of the welding jig. The expected outcomes of the study are to enhance the quality and efficiency of the angular welding process. Additionally, the designed welding jig provides ease of use for students, thereby reducing errors caused by human factors.